Fundamental parameters for the eclipsing binary AzV 73 in the small Magellanic Cloud - Ostrov, Pablo Gabriel (2001)
A CCD V light curve for the eclipsing binary star AzV 73 is presented. This new photometric observations are analysed together with previously published CCD I photometry from Udalski et al. (1998) and spectrographic data from Niemela & Bassino (1994), by means of the Wilson-Devinney code. It is found that this system is semi-detached, with an orbital inclination of roughly 86° and a separation of 42 R⊙. The sizes and masses are R1 = 11.53 ± 0.5 R⊙, M1 = 25.26 ± 0.7 M⊙, and R2 = 15.46 ± 0.4 R⊙, M2 = 21.96 ± 0.8 M⊙ for the primary and secondary components, respectively.